Clinical presentation and outcome of 20 fetuses with parvovirus B19 infection complicated by severe anemia and/or fetal hydrops. (19th June 2014) - Macé, Guillaume; Sauvan, Marine; Castaigne, Vanina; Moutard, Marie‐Laure; Cortey, Anne; Maisonneuve, Emeline; Garel, Catherine; Dhombres, Ferdinand; Boujenah, Jeremy; Mailloux, Agnès; Carbonne, Bruno
ABSTRACT Aim The aim of this study was to assess the prognosis of parvovirus B19 infection with severely anemic and/or hydropic fetuses according to initial ultrasound and biological criteria. Material and methods Retrospective study of 20 cases of congenital parvovirus B19‐proven infection (positive PCR) complicated by fetal anemia and/or hydrops was examined. Anemia was suspected on an elevated peak systolic velocity of the middle cerebral artery and was confirmed by fetal blood sampling. Results Survival rate was 70% (14/20) overall and 76% (13/17) for fetuses with one or more transfusions. When fetal effusion regressed after the transfusion, all 11 fetuses survived, and neonatal condition was favorable for all. Among the 14 live‐born children, there was one neonatal death and one admission to the neonatal care unit with no major complications. Conclusion Despite active management by transfusion in fetuses with parvovirus B19 infection, mortality remained substantial during the acute phase of anemia and fetal hydrops. Regression of effusion appears to be an important variable for prognosis. Non‐anemic forms exist with isolated refractory ascites or pleural effusion. Maternal mirror syndrome appears to reflect the intensity and persistence of the fetal anemia. © 2014 John Wiley & Sons, Ltd.